Recombinant Lipoprotein Rv1016c Derived from Mycobacterium tuberculosis Is a TLR-2 Ligand that Induces Macrophages Apoptosis and Inhibits MHC II Antigen Processing - Su, Haibo; Zhu, Shenglin; Zhu, Lin; Huang, Wei; Wang, Honghai; Zhang, Zhi; Xu, Ying (Frontiers in Cellular and Infection Microbiology, 2016)
TLR2-dependent cellular signaling in Mycobacterium tuberculosis-infected macrophages causes apoptosis and inhibits class II major histocompatibility complex (MHC-II) molecules antigen processing, leading to evasion of surveillance. Mycobacterium tuberculosis (MTB) lipoproteins are an important class of Toll-like receptor (TLR) ligand, and identified as specific components that mediate these effects. In this study, we identified and characterized MTB lipoprotein Rv1016c (lpqT) as a cell wall associated-protein that was exposed on the cell surface and enhanced the survival of recombinants M. smegmatis_Rv1016c under stress conditions. We found that Rv1016c lipoprotein was a novel TLR2 ligand and able to induce macrophage apoptosis in a both dose- and time-dependent manner. Additionally, apoptosis induced by Rv1016c was reserved in THP-1 cells blocked with anti-TLR-2 Abs or in TLR2−/− mouse macrophages, indicating that Rv1016c-induced apoptosis is dependent on TLR2. Moreover, we demonstrated that Rv1016c lipoprotein inhibited IFN-γ-induced MHC-II expression and processing of soluble antigens in a TLR2 dependent manner. Class II transactivator (CIITA) regulates MHC II expression. In this context, Rv1016c lipoprotein diminished IFN-γ-induced expression of CIITA IV through TLR2 and MAPK Signaling. TLR2-dependent apoptosis and inhibition of MHC-II Ag processing induced by Rv1016c during mycobacteria infection may promote the release of residual bacilli from apoptotic cells and decrease recognition by CD4+ T cells. These mechanisms may allow intracellular MTB to evade immune surveillance and maintain chronic infection.